Atomic structures of interfacial solute gateways to θ′ precipitates in Al-Cu alloys. (15th June 2021) - Chisholm, M.F.; Shin, D.; Duscher, G.; Oxley, M.P.; Allard, L.F.; Poplawsky, J.D.; Shyam, A.
Abstract: Many materials employed in critical structural applications depend upon metastable strengthening precipitates that transform or dissolve at elevated temperatures. Herein, aberration-corrected scanning transmission electron microscopy and first-principles calculations are used to accurately determine the atomic structure of the highly mobile, semi-coherent precipitate interfaces that control this process in the classic θ ′ (Al2 Cu) precipitate in the Al-Cu system. Semi-coherent {110} interfaces are found to be composed of an array of unexpected misfit dislocations that are arranged in two different structural units. Dislocations accommodate nearly all of the misfit between the Al matrix and strengthening phase. Cu is observed to segregate to the compressed edge of the dislocation cores at specific sites in this interface. First-principles calculations revealed the energetic landscape that facilitates these sites to become entry and exit gateways of Cu atoms in this semi-coherent interface. This investigation reveals critical features within semi-coherent interfaces that determine the thermal stability of precipitation-hardened alloys. Graphical abstract: Image, graphical abstract